CAMPUS-BASED STRATEGIES TO ADDRESS SUICIDE BEHAVIOURS AMONGST STUDENTS AT INSTITUTIONS OF HIGHER LEARNING IN SOUTH AFRICA - Tiisetso Aubrey; Mathibedi Frank (CV. RADJA PUBLIKA, 2024)
Suicide rates among adolescents and youth are increasing regardless of the interventions to lower the risks. Therefore, preventing suicides at institutions of higher learning is a top concern for public mental health. This paper explores strategies that may be adopted to reduce suicidal thoughts among students in South Africa. The study analysed previously published data on student suicide at institutions of higher learning. Purposive sampling technique was used by the researchers to collect secondary data from various research platforms that were specifically focused on the topic at hand. The following databases were utilized because they offer multi- and interdisciplinary scholarly literature: Google Scholar, Jstor, EbscoHost, Proquest, Scopus, and Sabinet. This review highlight that there are a variety of causes for students' suicidal thoughts, and these causes are individualised. Suicide prevention strategies such as gatekeeper training programs for suicidal behaviours, implementation of suicide prevention awareness programs within campuses, digitalisation of the programs, counselling and psychotherapy are some of the strategies that universities can adopt to reduce the suicidal thoughts among students. Given the complexity of suicide, prevention must be done with extreme prudence and urgency. The more the complexity of the suicide process is understood, the more the need for consistent, significant efforts to empirically support and evaluate the prevention strategies. It is therefore imperative to implement comprehensive and multi-sector preventative programs in order to minimize these risk factors and enhance protective variables to the greatest extent possible.